A house at the bottom of a lake eaudiobook - Malerman, Josh (Random House Audio, 2021)
From the  New York Times  bestselling author of  Bird Box  and  Malorie  comes a haunting tale of love and mystery, as the date of a lifetime becomes a maddening exploration of the depths of the heart. “Malerman expertly conjures a fairy tale nostalgia of first love, and we follow along, all too willingly, ignoring the warning signs even as the fear takes hold.”— Lit Reactor   The story begins: young lovers, anxious to connect, agree to a first date, thinking outside of the box.   At seventeen years old, James and Amelia can feel the rest of their lives beginning. They have got this summer and this summer alone to experience the extraordinary.   But they didn’t expect to find it in a house at the bottom of a lake.   The house is cold and dark, but it’s also their own.   Caution be damned, until being carefree becomes dangerous. For the teens must decide: swim deeper into the house—all the while falling deeper in love?   Whatever they do, they will never be able to turn their backs on what they discovered together. And what they learned:   Just because a house is empty, doesn’t mean nobody’s home.